Administrative Burden in the Semarang City One-Stop Integrated Service Unit - Ayudia Primantari, Farah Putri; Athalia Pranata Putri S. Meliala (HM Publisher, 2024)
This research aims to analyze the administrative burden faced by the Integrated Investment and One-Stop Service Agency in Semarang City in handling the investment process. Through a qualitative approach, data were collected through interviews with staff, document analysis, and direct observation of the administrative processes. The results indicate that UPTSP in Semarang City faces various challenges in managing the administration of investment. The administrative burden involves aspects such as the completeness of application documents, coordination with relevant agencies, project feasibility analysis, and decision-making. Although UPTSP has implemented the One-Stop Service system to enhance efficiency, there are still obstacles related to data integration between agencies and the expansion of integrated services. This research provides an in-depth understanding of the administrative burden faced by UPTSP in Semarang City, providing a foundation for the development of more effective strategies to improve performance and services for business actors. The implications of these findings can serve as a reference for stakeholders, the city government, and UPTSP itself in designing policies that support increased efficiency and effectiveness in managing investments in Semarang City.